RENEWABLE ENERGY RESOURCES IN AGRICULTURE: POTENTIAL AND LEGAL FRAMEWORK IN THE REPUBLIC OF SERBIA - Nadežda Ljubojev; Marijana Dukić-Mijatović; Željko Vojinović (Ekonomika Poljoprivrede (1979), 2018)
The disappearance of natural resources, development of environmental awareness and need to rationalize their spending, and in order to reduce the cost of energy production, caused an increasing need for the development and use of renewable energy sources (RES).Larger use of RES would provide energy security and lower energy imports. Of all forms of RES in R. Serbia, the biomass energy potential comes first. There has been considered legal framework relevant to the use of RES at the European level and within the boundaries of the R. Serbia. The authors point to the need for further harmonization of domestic legislation with global and European trends in the field of RES, as well as obligations from ratified international documents and the European integration process. The article also shows the potential of RES in agriculture as well as the actual state of exploitability in R. Serbia. Increasing the use of RES in R. Serbia can help diversify Serbians energy supply, create growth and jobs, and lower greenhouse gas emissions.